Investigation and comparison of tires perfomance on ice - Ružinskas, Andrius; Sivilevičius, Henrikas (International Conference “Environmental Engineering”, 2017)
The risk of accident increases significantly when tire rolls on ice comparing to the dry surface. The vehicle tire becomes the main component of force transmission to the road and necessity of investigating the tire behavior becomes of high importance. This paper presents results of tire force transmission measurement with two different winter tires at the same operating conditions. Longitudinal and lateral force coefficient characteristics as the functions of slip ratio and slip angle are presented and discussed. The results showed a different lateral and longitudinal performance because of different tread pattern and rubber compound.